Pemberdayaan Masyarakat Desa Bojo Melalui Budi Daya Maggot Sebagai Solusi Mengatasi Sampah Organik Rumah Tangga - Sudarmono, Sudarmono; Busman, Aqilah Luthfiah; Edo, Trisno; Yusril, Yusril; Beddu, Megawati; Ilahi, Andi Alfianto Anugrah (JGEN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Bojo Village in Mallusetasi District, Barru Regency, South Sulawesi, faces problems with household waste management, especially organic waste scattered on the beach and near residential areas. This waste causes environmental pollution and has a negative impact on public health. The proposed solution is maggot cultivation from Black Soldier Fly (BSF) as an effective and economically valuable organic waste management method. Maggot can decompose organic waste quickly, produce high-quality organic fertilizer (kasgot), and become nutritious animal feed. The program combines reduce and recycle approaches to create environmental benefits and economic opportunities. Through maggot cultivation, the community is expected to be able to reduce the volume of waste, increase soil fertility, and create new businesses that increase local income.